2016
DOI: 10.1089/dia.2016.0105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic Messaging on Glucose Control and Hospital Admissions Among Patients with Diabetes

Abstract: Background: Electronic messaging (EM) is increasingly utilized among patients with diabetes, but it is unclear whether it is associated with improved glycemic control, hospital admissions, or emergency visits. Methods: Patients who were seen over a 1 year period at an academic endocrinology clinic with a diagnosis of diabetes were categorized according to portal activation and whether EMs were actually sent. The association between EM and HbA1c and inpatient or emergency department (ED) visits was further char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…Thus, it does not describe the effectiveness of secure messaging in community-based outpatient settings. In a study conducted in an academic setting with a small number of patients, messaging was associated with improved HbA 1c control but increasing the frequency of messaging was not associated with better control (17). This study did not account for a nonlinear dose-response relationship, however.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, it does not describe the effectiveness of secure messaging in community-based outpatient settings. In a study conducted in an academic setting with a small number of patients, messaging was associated with improved HbA 1c control but increasing the frequency of messaging was not associated with better control (17). This study did not account for a nonlinear dose-response relationship, however.…”
Section: Discussionmentioning
confidence: 91%
“…Messaging with providers could be used as a substitute for traditional office visits and thus be cost saving for patients and payers (5). Studies of patients with diabetes found that increased use of outpatient and inpatient care (13)(14)(15) improved diabetes care processes and outcomes (16)(17)(18)(19)(20) associated with the use of patient portal or secure messaging with providers. However, these studies were conducted mainly as clinical trials of messaging linked with diabetes management programs or in integrated delivery organizations, which may not be representative of how messaging is used in community settings.…”
mentioning
confidence: 99%
“… 20 ICT has been shown to improve self-management and satisfaction of care in various settings, with evidence of improved health outcomes in chronic disease populations. 21 - 23 More recently, ICT has spread to the dialysis population with the advent of online self-management support tools and advances in telemedicine technologies. 24 - 26 …”
Section: Discussionmentioning
confidence: 99%
“…In particular, secure messaging is a unique aspect within patient portals that may facilitate patient self-management, shared decision making, and patient satisfaction by allowing patients more opportunities to communicate with providers [9]. Secure messaging has been associated with favorable clinical outcomes, specifically in studies examining diabetes management, in which patients who engage in secure messaging have lower hemoglobin A 1c values [1,8,10-15].…”
Section: Introductionmentioning
confidence: 99%